Picturing American War on Iraq: A Visual Discourse Analysis of Decoding ‘Death’ in the Photojournalist’s Lenses - Halawachy, Dr.Huda (International Journal of Language and Literary Studies, 2022)
For me, the strength of photography lies in its ability to evoke humanity. If war is an attempt to negate humanity, then photography can be perceived as the opposite (James Nachtwey) (https://www.quotes.net/mquote/102671) Death, though certain, is horrible and scary when it comes to the fact that it is due to war and armed conflict for decades in a spot like Iraq. People relate war to history through photography (Topba?, 2011). The current paper fundamentally is a portal to mirroring the photojournalist’s shots in making meaning of death by letting the audience read what is unspeakable in photos. Basically, a collection of (19) photos captured by three World Press Prizes winners, photojournalists – Lynsey Addario, Adam Ferguson, and Ivor Prickett – (among others) – were analysed, focusing on their galleries of photos and the media on the the American war in Iraq. Doing visual discourse analysis in photos, though of different war eras in Iraq, and a semiotic approach is radically adopted in the analytical part to break the code of Death in the selected photos. Icons and symbols are potentially workable clues for thematizing non-physical death in a place of the world which is devastated thoroughly. It is the bombarded questions on which the current study is based: (1) How could the abstract death be approached linguistically in war photography? (2) Is it the shot that nearly kills the photojournalist being in the front line making them feel a momentum death as the casualties? (3) Is the photojournalist’s role in war an eyewitness of the casualties’ physical bloody death or there could be other hidden deaths that are decoded in the shots?, and (4) Are the camera’s shots reliable enough to speak the messages on death in wartime? The study transpired a variety of deaths in the iconic and symbolic shots of the American war in Iraq. Other academic shots for future works on visual discourse, I remain capturing.